Reconstruction of the Election Simultaneity Model through the Constitutional Court Decision Number 135/PUU-XXII/2024: Constitutional or Unconstitutional? - Afandi, M; Amboro, F. Yudhi Priyo; Seroja, Triana Dewi (Journal of Law, Politic and Humanities, 2025)
The simultaneous election model that separated the implementation of national and local elections has created various problems, such as election worker fatigue, logistical burdens, and limited attention to local issues. Constitutional Court Decision No. 135/2024 subsequently corrected this model by establishing a new arrangement that separates the conduct of National Elections and Regional Elections. This study was a normative legal research employing qualitative juridical analysis aimed at examining the effectiveness of the previous simultaneous model, testing the constitutionality of the new model, and analyzing its implications for the term of office of Regional Heads and local parliament members (DPRD) elected in 2024. The findings show that the previous simultaneous model was ineffective, the new model has a strong constitutional basis, and the most rational solution to its transitional implications is to shorten the term of office of Regional Heads and DPRD members elected in 2024 and to hold Regional Elections in 2028. In this regard, it is recommended to amend the Election Law and the Regional Election Law and to regulate the transitional period in accordance with constitutional principles.